Coffee Area (Subak Abian Tri Guna Karya Kintamani Bangli) Based Waste Management Potential to Generate Renewable Energy Sources and Nutrition - Sucipta, INyoman (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 2 No 2 (2015), 2015)
Bali island has 5.632.86 km2 area with a total area of 36.298 hectares of coffee farm in 2004with production 3.696.206 15386.405 tons of Arabica coffee and Robusta coffee produces tonsof waste is high enough. The results of the proximate analysis of robusta coffee waste containingprotein, crude fiber and fat is high at 6.67 to 12.43% crude protein, fiber kasar11,05-21,40%, fat1.04 to 1.07%, while the calcium 0 , 21 to 0.34% and 0.02-0.07% phosfor.Materials (coffee waste) inserted through the container revenue in accordance with thetreatment, then allowed to ferment anaerobically for 35 days, if the bio-gas already formed inlarge volume, then the bio-gas flow from the inner tube to cleaners tube which then exits througha gas hose. Bio-gas has started to form when the water in the U manometer and hose materialspointer moves upward.Parameters measured were the temperature of the fermentation medium was measured with athermometer scale 0-100oC. Volume of bio-gas can be shown on the hose raw material pointerwas the changes of the surface of raw material height multiplied by its width. Gasbio pressureinside the bioreactor was measured using a manometer U scaleD 3-3 cm. gasbio production wasmeasured by thermik properties of the gas or through the ideal gas equation (Sutanto, 1982).Technical analysis measured through the strength of materials, dimensions and weight. Thecontent of gasbio is observed from methanogenic process is methane gas, and of the hydrolysisand acidification processes was carbon dioxide gas using a Shimadzu GC-7A kromatograf modelChemical analysis of coffee waste and bio-gas as byproduct was crude fiber, nitrogen, fattyacids, calcium, phosphorus, iron, magnesium, manganese, potassium, sodium and zinc as well ascaffeine using atomic spetrophotometes.Handling of coffee waste using region-based bioreactors (Subak Abian Tri to workKintamani Bangli) generate renewable energy, a source of nutrients and bioactive and spawned aculture of energy saving, clean and healthy
Keywords: Waste management; energy sources; nutrition